Умный парник на ARDUINO в связке с ANDROID-устройством - Цыбусов, Н. К.; Битченко, О. Н. (ХНУРЕ, 2018)
The relevance of the project "Smart Greenhouse" as an independent unit and as part of the project "Smart Home" or "Smart City" is very high today, when we are no longer just learning about the Internet from blue screens of our gadgets, and already partly using the IoT elements at home. The truth so far, it's still a little like a single coherent system of operation of all our instruments, but the need has already matured.
Keywords: умный парник; arduino; android